More on Phantom Bidding - Ruqu Wang; Parimal Kanti Bag; Emim Murat Dinlersoz (Queen's University, Department of Economics, 1998)
A phantom bidding model is analyzed for a sale auction. The following questions are addressed: the effects of phantom bidding on overall social welfare and buyers' profits. It is shown that social welfare may increase or decrease as the auctioneer switches from the fixed reserve price policy to phantom bidding. The buyers' profits will increase whenever social welfare increases.
Keywords: D44; 330; English Auction; Phantom Bidding; Fixed/Flexible Reserve Price